A carbon efficiency method to evaluate the environmental burden of a workshop based on energy footprint and carbon footprint. (2014) - Zhang, Chaoyang; Jiang, Pingyu; Zhang, Lei; Li, Weidong; Gu, Peihua
No abstract available